Value relevance of the new environmental enforcement regime in China - Sam, Abdoul G.; Zhang, Xiaodong (Journal of Corporate Finance, 2020)
Curbing environmental pollution has become a key priority in China, as reflected in the adoption of policies such as “New Normal” and the takeover of regulatory environmental enforcement by the top leadership of the central government in 2015. In this paper, we use a dataset of publicly-traded firms in the Shanghai and Shenzhen stock exchanges and the event study methodology to gauge the reaction of the investor class to the new environmental enforcement regime. Our results indicate that, together, the announcement and implementation of the new enforcement regime spurred a significant decline of over $29 billion in shareholder value of polluting companies, suggesting that capital market participants expect increased regulatory costs for targeted companies. We also find that neither political connections nor firm size mitigated the severity of the market losses. Instead, larger firms and state-owned enterprises with excess capacity experienced bigger declines in market value.